Involvement of estrogen receptor-β in farrerol inhibition of rat thoracic aorta vascular smooth muscle cell proliferation - Li Qun-yi; Chen Li; Zhu Yan-hui; Zhang Meng; Wang Yi-ping; Wang Ming-wei (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of farrerol, a major active component isolated from a traditional Chinese herb “Man-shan-hong” (the dried leaves of Rhododendron dauricumL) on fetal bovine serum (FBS)-induced proliferation of cultured vascular smooth muscle cells (VSMCs) of rat thoracic aorta. Methods: VSMCs proliferation, DNA synthesis and cell cycle progression were studied using the MTT assay, bromodeoxyuridine (BrdU) incorporation and flow cytometry, respectively. The mRNA levels of cell cycle proteins were quantified using real-time RT-PCR, and the phosphorylation of ERK1/2 was determined using Western blotting. Reporter gene and receptor binding assays were employed to study the interaction between farrerol and estrogen receptors (ERs). Results: Farrerol (0.3–10 μmol/L) inhibited VSMC proliferation and DNA synthesis induced by 5% FBS in a concentration-dependent manner. The effects were associated with G1 cell cycle arrest, down-regulation of cell cycle proteins and reduction in FBS-induced ERK1/2 phosphorylation. Using a reporter gene, it was found that farrerol (3 μmol/L) induced 2.1-fold transcription of ER. In receptor binding assays, farrerol inhibited the binding of [3H]estradiol for ERα and ERβ with IC50 values of 57 μmol/L and 2.7 μmol/L, respectively, implying that farrerol had a higher affinity for ERβ. Finally, the inhibition of VSMC proliferation by farrerol (3 μmol/L) was abolished by the specific ERβ antagonist PHTPP (5 μmol/L). Conclusion: Farrerol acts as a functional phytoestrogen to inhibit FBS-induced VSMC proliferation, mainly via interaction with ERβ, which may be helpful in the treatment of cardiovascular diseases related to abnormal VSMCs proliferation.